Capital accounting and liabilities problems in the context of economic processes reforming and international financial reporting standards introducing - X. Yu. Kotova; N. N. Shakirova (Вестник университета)
Reform in the Russian Federation raises a number of problems, including the regulation of capital and liabilities accounting. The object of the study is the International Financial Reporting Standards impact on the domestic accounting system development, reflecting the economic processes globalisation and digitalisation, the emergence of new accounting objects and increasing requirements for the reporting quality. The essence of newly emerging accounting categories was analysed in the article, the definitions of “liabilities” in the International Financial Reporting Standards and domestic practice were compared. It was identified, that gaps in the capital and liability accounting caused by the lack of a unified conceptual apparatus, the presence of estimated values, the use of an accountant professional judgment that affects the information quality in reporting, the backlog of legislative regulation in terms of accounting for digital objects as authorized capital. The accounting and reporting issues in the reporting of operations of the business social orientation were considered. Possible ways of solving the liability accounting problems are presented, including the conceptual apparatus unification, the accounts chart modernisation, the development of recommendations regarding the application of the accountant professional judgment, the expansion of requirements for the information list on the economic entity activities presented in the accounting (financial) statements, and the International Financial Reporting Standards application.